Study Of The Composition Of The Secondary Product Of The Pyrolysis Process And The Synthesis Of Polymethylene-Anthracenesulphoxicolate - Habiyev F.M; Nurmonov S.E; Qodirov O.SH; Kenjaev A.Q (Zien Journals, 2024)
Today, the Ustyurt gas chemical plant in our Republic is not processing a large amount of byproduct waste, which has a negative influence on the environment. The composition of these wastes was studied by vacuum fractionation at high temperature, and the obtained products were analyzed by physico-chemicall. Polymethyleneanthacene sulfoacids (SOF-1 and SOF-2) with a spatial structure were synthesized by polycondensation of the obtained mono- and dianthracene sulfoacids with formalin. Process parameters were studied.
Keywords: pyrolysis; secondary product; chemical composition